Stem cell activity shapes the pleiotropic effects of IFN-γ and TGF-β in autoimmune diseases, infections, and cancer, and drives autoimmune flares and remissions - Elkoshi, Zeev (Frontiers in Immunology, 2025)
This work introduces stem cell activity as a central factor contributing to the pleiotropic effects of IFN-γ and TGF-β1, as well as to the fluctuations of autoimmune diseases (AIDs) between flares and remissions. Analysis of published data on hair follicle immune privilege indicates that immune protection is not an inherent feature of quiescent stem cells, as previously proposed, but instead depends on the specific pathways that regulate quiescence. While both IFN-γ and high levels of TGF-β1 induce stem cell quiescence, they exert opposite effects on immune privilege: IFN-γ upregulates MHC-I expression, whereas TGF-β1 downregulates it. Similar mechanisms apply to hematopoietic stem cell niches in the bone marrow. Moreover, cytokines such as IGF-1 and α-MSH, which enhance stem cell activity, also downregulate MHC-I. Different concentrations and combinations of these cytokines can promote or suppress stem cell activity and preserve or disrupt immune privilege, underscoring their multifaceted nature. Two mechanisms may contribute to the pleiotropic effects of IFN-γ and TGF-β1: opposing effects on bone marrow activity, with IFN-γ and high TGF-β1 acting in contrast, and differential effects of IFN-γ on immune attack intensity in the bone marrow versus the target tissue during AID. Stem cell dynamics also shape the course of AIDs: high stem cell activity supports tissue regeneration and remission, whereas quiescence together with tissue destruction by autoimmune attacks drives flares. A clear correlation emerges between the effects of various agents on stem cell activity and clinical outcomes in AIDs, highlighting the central role of stem cell activity in their pathogenesis. A proposed TGF-β1 gradient between protected stem cell reservoirs (hair follicle bulge, bone endosteal niches) and less protected regions enables simultaneous preservation of stem cells and regeneration of damaged tissue.